'Unregarded age': texts and contexts for elderly characters in English renaissance drama, c.1480-1625 - Sheldon, DSK (2000)
This study seeks to provide historical and literary contexts for elderly characters from English play-texts c.1580 to 1625. Its primary aim, from a literary perspective, is to draw attention to the ways that a better understanding of elderly characterisation can enrich the appreciation of much-studied play-texts, and to indicate some interesting features of more obscure ones. Its secondary aim is to suggest the value, for social historians of old age in early modern England, of play-texts as social evidence. I have examined most of the published extant play-texts of the period, and have found approximately 150 of these to be relevant (the most important of these are listed in the Appendix). Because of the problems of handling all aspects of such a large amount of material, I have chosen to consider the plays chiefly as texts to be read, with little reference to their performative aspects. However, I analyse the dramas as literary as well as social documents. Specific plays provide illustrations for observations and support for various hypotheses about dramatic representations of the elderly. In some instances, I address plays which have received little critical attention. The thesis falls into two parts. In the first three chapters, I discuss the socio-historical, cultural and non-dramatic literary contexts for representations of elderly men and women in play-texts. In chapters four through seven, I examine elderly characters in specific role or relationship categories: as sovereigns and magistrates, in sexual and marital relationships, and as parents. In the final chapter, I offer a detailed analysis of The Old Law by Thomas Middleton and William Rowley.